Qualitative Analysis of Policies and Social, Economic, and Cultural Factors on HIV/AIDS Incidence Rates - Muliana Mansur; Fauzi Almari; Zefan Adiputra Golo; Anton Kristijono (Jurnal Kesehatan, 2026)
Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) remains a major public health problem in Indonesia, with marked disparities in prevention and treatment across regions. This study aims to examine government policies and the social, economic, and cultural factors influencing HIV/AIDS incidence through comparative case studies in North Maluku, Yogyakarta, and Central Java. This research used a qualitative multiple-case study design. Data were collected through in-depth interviews, focus group discussions, and a review of secondary documents and program data. The study population comprised key stakeholders involved in HIV prevention and care, including provincial and district health authorities, facility-based providers, non-governmental organizations, peer educators, and representatives of key populations receiving services. Participants were selected using purposive sampling, complemented by snowball sampling to reach hard-to-access community actors. Data were analyzed using thematic analysis through data reduction, data display, and conclusion drawing. Findings indicate that the implementation of the Healthy Indonesia with a Family Approach Program has been uneven. In North Maluku, HIV testing coverage among transgender women and their partners remains below 60%, while reported incidence continues to increase. In Yogyakarta, spatial and social dynamics shape transmission patterns, with geographic information system analysis identifying persistent hotspots associated with sex work areas. Central Java demonstrates comparatively stronger outcomes through collaborative governance, where egalitarian partnerships among health authorities, Non-Governmental Organizations, and peer groups expand access to services despite resource constraints. The study concludes that national policies are comprehensive, but effective control requires locally tailored adaptation, stronger intersectoral collaboration, and meaningful community participation to reduce disparities and enhance program sustainability.